A method for preparing high-performance near-infrared perovskite film in air
By doping tetrabutylamine hexafluorophosphate and PMMA in the antisolvent of the perovskite film, and using spin coating method and annealing crystallization technology, the problem of poor stability of perovskite optoelectronic devices in the air is solved, significantly improving the fluorescence intensity and stability of the film.
Patent Information
- Application Number
- CN202210024343.6
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2022-01-07
- Publication Date
- 2025-03-18
- Estimated Expiration
- 2042-01-07
AI Technical Summary
Perovskite optoelectronic devices have poor stability in the air, resulting in the device working time and degradation in humid air environments, increasing the preparation cost.
The film was formed on the substrate by doping tetrabutylamine hexafluorophosphate and polymethyl methacrylate (PMMA) in the antisolvent of the perovskite film, and the stability of the film was improved by annealing and crystallization.
Improve the stability and fluorescence intensity of perovskite films in humid air environments, which increase the fluorescence intensity to 15 times that of untreated films, and the fluorescence intensity only decreases to 98% of the initial during long storage in the air.
Smart Images

Figure CN114464739B_ABST
Abstract
Description
Technical Field
[0001] The invention relates to the technical field of photoluminescence, and in particular to a method for preparing a high-performance near-infrared perovskite film in air. Background Art
[0002] Perovskite is a highly efficient luminescent material. It has excellent properties such as high color purity, adjustable emission wavelength covering the entire visible light region, and ultra-high photoluminescence quantum yield, and is widely used by researchers in the field of optoelectronic devices. It also has advantages such as high performance and easy preparation.
[0003] However, the perovskite active layer, which is the core of perovskite optoelectronic devices, currently has the following problems:
[0004] (1) The perovskite active layer is very sensitive to water vapor and oxygen, and will degrade if exposed to humid air for a long time. Therefore, almost all perovskite films are prepared in a glove box with a nitrogen atmosphere, which undoubtedly increases the preparation cost of the device.
[0005] (2) The working environment of perovskite photoelectric devices is mostly air. Due to the poor stability of perovskite in air, the working time of the device is much lower than that of similar products, such as silicon-based solar cells and OLEDs.
[0006] (3) Most large-scale semiconductor processes are carried out in an air environment. If perovskite is introduced into commercial large-scale production, under current conditions, in order to obtain high-quality perovskite optoelectronic devices, the entire production line needs to be placed in a nitrogen environment, which undoubtedly increases the cost of commercialization. In other words, it is imperative to prepare efficient and stable perovskite films in air. However, the luminous efficiency and stability of perovskite films prepared directly in air without any treatment are greatly reduced compared to those prepared in a glove box. In a high humidity environment, the luminous intensity of perovskite films prepared in air is even only one-tenth of that prepared in a glove box. Summary of the invention
[0007] In view of the above problems, the present invention provides a method for preparing a perovskite film in the air, which can prepare a perovskite film with high fluorescence intensity and good stability in the air by doping the anti-solvent required for preparing the perovskite film.
[0008] In order to solve the above technical problems, the present invention provides the following technical solutions:
[0009] A method for preparing a perovskite film in air, the method comprising four steps: (1) preparing a substrate and preparing a perovskite precursor solution; (2) doping and preparing an anti-solvent; (3) spin coating the perovskite on the substrate using a spin coating method; (4) annealing and crystallizing to form a perovskite film; the doping materials in the anti-solvent are tetrabutylammonium hexafluorophosphate and polymethyl methacrylate.
[0010] Preferably, the preparation of the substrate specifically comprises: cutting the substrate into square substrates, cleaning the substrates using an RCA cleaning method, and then drying the substrates;
[0011] The perovskite precursor solution is prepared by dissolving monovalent cation halide and lead halide and / or tin halide powders in a mixed solution of N,N-dimethylformamide and dimethyl sulfoxide, and rapidly dissolving them by magnetic stirring or ultrasound, wherein the concentration of monovalent cation lead halide and / or tin in the obtained perovskite precursor solution is 0.2-1M;
[0012] The doping and preparation of the anti-solvent: tetrabutylamine hexafluorophosphate and 2% PMMA chlorobenzene solution are added to the anti-solvent, and mixed evenly by magnetic stirring or ultrasound, and the doping concentrations of the obtained solution are: 0.1-0.7 mg / ml tetrabutylamine hexafluorophosphate and 0.1%-0.4% PMMA;
[0013] The spin coating of the perovskite film uses a two-step spin coating method, and the doped anti-solvent is added dropwise 9 to 11 seconds before the second step is completed;
[0014] The annealing crystallization specifically includes: transferring the spin-coated substrate to a hot stage for annealing crystallization to form a perovskite film.
[0015] Preferably, the anti-solvent is one or more of toluene, chlorobenzene, dichloromethane or ethyl acetate.
[0016] Preferably, the volume ratio of N,N-dimethylformamide to dimethyl sulfoxide is 9:1.
[0017] Preferably, the substrate is one of an ITO or FTO conductive glass substrate, p-type silicon, n-type silicon, silicon dioxide, a flexible substrate or graphene.
[0018] Preferably, the two-step spin coating method is as follows: dripping the perovskite precursor solution on the substrate, wherein the first step of spin coating takes 9 to 11 seconds and the spin coating speed is 950 to 1100 rpm, and the second step of spin coating takes 19 to 21 seconds and the spin coating speed is 4900 to 5100 rpm.
[0019] Preferably, the annealing crystallization temperature is 95-105° C., and the annealing time is 9-11 min. After completion, a well-crystallized perovskite film is obtained that can be stably stored for a long time in an air environment.
[0020] A perovskite crystalline material is formed by annealing and crystallization according to the method for preparing a perovskite film in air. The general formula of the perovskite crystalline material is ABX3, wherein A is a monovalent cation, B is a divalent metal cation, and X is a halogen anion.
[0021] Preferably, the monovalent cation is Rb + 、Na + , K + , Cs + 、(NH2)2CH + or CH3NH3 + One or more of; wherein the divalent metal cation is Pb 2+ and / or Sn 2+ ; The halogen anion is Cl - Br - and I - One or more of .
[0022] Beneficial effects obtained by the present invention:
[0023] (1) It can be prepared in a humid air environment instead of a glove box: by doping PMMA in an anti-solvent, the perovskite can be normally crystallized into a film in an air environment with a humidity of less than 70%;
[0024] (2) The prepared perovskite film has high fluorescence intensity: by doping with PMMA, the surface defects of the perovskite can be passivated, and the fluorescence intensity of the perovskite can be increased to 3.5 times that of the untreated perovskite film. By further doping with tetrabutylammonium hexafluorophosphate, the shortcomings of PMMA in carrier transport can be compensated, and the surface defects of the perovskite can also be passivated, and the fluorescence intensity can be increased. The superposition of the effects of the two materials can produce an effect of 1+1 being far greater than 2. Under the condition of 40% air humidity, the fluorescence intensity of the perovskite film after anti-solvent doping can be increased to 15 times that of the untreated perovskite film.
[0025] (3) Good stability in air environment: The prepared perovskite film can be stored in an air environment with a carbon dioxide concentration of about 40% for one month and still maintain a fluorescence intensity close to the initial level. BRIEF DESCRIPTION OF THE DRAWINGS
[0026] Figure 1 This is a comparison chart of the photoluminescence intensity of the MAPbI3 perovskite film before and after anti-solvent doping in the present invention.
[0027] Figure 2This is a curve showing the change in fluorescence intensity of the MAPbI3 perovskite film before and after anti-solvent doping in the present invention when placed in an air environment for 28 days.
[0028] Figure 3 This is a scanning electron microscope image of the surface morphology of the MAPbI3 perovskite film after anti-solvent doping in the present invention.
[0029] Figure 4 This is a scanning electron microscope image of the surface morphology of the MAPbI3 perovskite film before anti-solvent doping in the present invention.
[0030] Figure 5 This is a comparison chart of the photoluminescence intensity of the MAPbBr3 perovskite film before and after anti-solvent doping in the present invention.
[0031] Figure 6 This is a curve showing the change in fluorescence intensity of the MAPbBr3 perovskite film before and after anti-solvent doping in the present invention when placed in an air environment for 28 days.
[0032] Figure 7 This is a scanning electron microscope image of the surface morphology of the MAPbBr3 perovskite film after anti-solvent doping in the present invention.
[0033] Figure 8 This is a scanning electron microscope image of the surface morphology of the MAPbBr3 perovskite film before anti-solvent doping in the present invention.
[0034] Fig. 9 The scanning electron microscope images are of the surface morphology of MAPbI3 perovskite films grown on different substrates in the present invention.
[0035] Fig.10 is the MAPb after anti-solvent doping in the present invention 0.9 Sn 0.1 Scanning electron microscope image of the surface morphology of I3 perovskite film.
[0036] Fig.11 MAPb before and after antisolvent doping in the present invention 0.9 Sn 0.1 Comparison of photoluminescence intensity of I3 perovskite films.
[0037] Fig.12 MAPb before and after antisolvent doping in the present invention 0.9 Sn 0.1 Fluorescence intensity change curve of I3 perovskite film placed in air environment for 28 days.
[0038] Fig.13 The anti-solvent doped Cs 0.05 FA 0.9 MA 0.05 PbI 2.85 Br0.15 Scanning electron microscopy image of the surface morphology of perovskite film.
[0039] Fig.14 is the Cs before and after the antisolvent doping in the present invention 0.05 FA 0.9 MA 0.05 PbI 2.85 Br 0.15 Comparison of photoluminescence intensity of perovskite films.
[0040] Fig.15 is the Cs before and after the antisolvent doping in the present invention 0.05 FA 0.9 MA 0.05 PbI 2.85 Br 0.15 The fluorescence intensity change curve of the perovskite film after being placed in an air environment for 28 days.
[0041] Fig.16 The MA after anti-solvent doping in the present invention 0.9 K 0.1 PbI 2.8 Cl 0.2 Scanning electron microscopy image of the surface morphology of perovskite film.
[0042] Fig.17 MA before and after anti-solvent doping in the present invention 0.9 K 0.1 PbI 2.8 Cl 0.2 Comparison of photoluminescence intensity of perovskite films.
[0043] Fig.18 MA before and after anti-solvent doping in the present invention 0.9 K 0.1 PbI 2.8 Cl 0.2 The fluorescence intensity change curve of the perovskite film after being placed in an air environment for 28 days. DETAILED DESCRIPTION
[0044] The specific implementation modes of the present invention are further explained in detail below through the description of embodiments, so as to help those skilled in the art to have a more complete, accurate and in-depth understanding of the inventive concept and technical solution of the present invention.
[0045] Example 1: Under the condition of air humidity of 40%, a perovskite film was prepared as follows:
[0046] Step 1: Prepare a 1 cm×1 cm square p-type silicon substrate, clean it using an RCA cleaning method, and then dry it.
[0047] Step 2: Dissolve 48 mg of methylamine iodide (CH3NH3I, MAI) and 138 mg of PbI2 powder in a mixed solution of N,N-dimethylformamide (DMF) and dimethyl sulfoxide (DMSO) with a volume ratio of 9:1, where DMF is 635 μl and DMSO is 72 μl, and dissolve them quickly by ultrasound. The concentration of the resulting methylamine lead iodide (CH3NH3PbI3, MAPbI3) perovskite precursor solution is 0.3M.
[0048] Step 3: Add 0.5 mg of tetrabutylamine hexafluorophosphate (TBAPF-6) and 100 μl of 2% polymethyl methacrylate (PMMA) chlorobenzene solution into 1 ml of ethyl acetate, and mix them evenly by magnetic stirring or ultrasound. The doping concentrations of the resulting solutions are: tetrabutylamine hexafluorophosphate 0.5 mg / mL and PMMA 0.2%.
[0049] Step 4: Use a two-step spin coating method to drop 20 μl of the precursor solution on the substrate. The first step lasts for 10 s at a speed of 1000 rpm, and the second step lasts for 20 s at a speed of 5000 rpm. 150 μl of anti-solvent is added 10 s before the completion of the second step.
[0050] Step 5: Transfer the spin-coated substrate to a hot stage, set the temperature to 100°C, and anneal for 10 minutes. After completion, a well-crystallized MAPbI3 perovskite film is obtained that can be stably preserved for a long time in an air environment.
[0051] The final film thickness is about 90nm, and the emission peak is at 760nm. Figure 1 This is a comparison of the photoluminescence intensity spectra of MAPbI3 perovskite film before and after antisolvent doping. By doping with tetrabutylammonium hexafluorophosphate and PMMA, the fluorescence intensity of MAPbI3 perovskite film increased by 15 times; Figure 2 This is a comparison chart of fluorescence intensity after long-term placement in the air. By doping with tetrabutylammonium hexafluorophosphate and PMMA, after being stored in the air for 28 days, the fluorescence intensity of the MAPbI3 perovskite film only decays to 98% of the initial fluorescence intensity, which is much better than the undoped MAPbI3 perovskite film. Figure 3 and Figure 4 The surface morphology SEM images of MAPbI3 perovskite before and after antisolvent doping are shown respectively.
[0052] Doping with PMMA can ensure that MAPbI3 perovskite can crystallize and form a film normally in a humid air environment. Both PMMA and tetrabutylammonium hexafluorophosphate can passivate the surface defects of MAPbI3 perovskite and enhance the fluorescence intensity of MAPbI3 perovskite. In addition, doping with tetrabutylammonium hexafluorophosphate can make up for the shortcomings of PMMA in carrier transport. The combined effects of the two materials can produce an effect of 1+1 being far greater than 2.
[0053] Example 2: Under the condition of air humidity of 70%, a perovskite film was prepared as follows:
[0054] Step 1: Prepare a 1 cm × 1 cm square ITO conductive glass substrate, clean it using the RCA cleaning method, and then dry it.
[0055] Step 2: Dissolve 112 mg of methylammonium bromide MABr and 367 mg of PbBr2 powder in a mixed solution of N,N-dimethylformamide (DMF) and dimethyl sulfoxide (DMSO) with a volume ratio of 9:1, where DMF is 635 μl and DMSO is 72 μl, and dissolve them quickly by ultrasound. The concentration of the resulting methylamine lead bromide (CH3NH3PbBr3, MAPbBr3) perovskite precursor solution is 1M.
[0056] Step 3: Add 0.5 mg of tetrabutylamine hexafluorophosphate and 100 μl of 2% PMMA chlorobenzene solution into 1 ml of ethyl acetate, and mix them evenly by magnetic stirring or ultrasound. The doping concentrations of the resulting solutions are: 0.5 mg / mL tetrabutylamine hexafluorophosphate and 0.2% PMMA.
[0057] Step 4: Use a two-step spin coating method to drop 50 μl of the precursor solution on the substrate. The first step lasts for 10 s at a speed of 1000 rpm, and the second step lasts for 20 s at a speed of 5000 rpm. Add 1 ml of anti-solvent 10 s before the completion of the second step.
[0058] Step 5: Transfer the spin-coated substrate to a hot stage, set the temperature to 100°C, and anneal for 10 minutes. After completion, a well-crystallized MAPbBr3 perovskite film is obtained that can be stably preserved for a long time in an air environment.
[0059] The final film thickness is about 300nm, and the emission peak is at 520nm. Figure 5 This is a comparison of the photoluminescence intensity spectra of MAPbBr3 perovskite film before and after antisolvent doping. By doping with tetrabutylammonium hexafluorophosphate and PMMA, the fluorescence intensity of MAPbBr3 perovskite film increased by 13 times; Figure 6This is a comparison chart of fluorescence intensity after long-term placement in the air. By doping with tetrabutylammonium hexafluorophosphate and PMMA, after being stored in the air for 30 days, the fluorescence intensity of the MAPbBr3 perovskite film only decays to 98% of the initial fluorescence intensity, which is much better than the undoped MAPbBr3 perovskite film. Figure 7 and Figure 8 The surface morphology SEM images of MAPbBr3 perovskite before and after antisolvent doping are shown respectively.
[0060] Doping with PMMA can ensure that MAPbBr3 perovskite can crystallize and form a film normally in a humid air environment. Both PMMA and tetrabutylammonium hexafluorophosphate can passivate the surface defects of MAPbBr3 perovskite and enhance the fluorescence intensity of MAPbBr3 perovskite. In addition, doping with tetrabutylammonium hexafluorophosphate can make up for the shortcomings of PMMA in carrier transport. The combined effects of the two materials can produce an effect of 1+1 being far greater than 2.
[0061] Example 3: The rest is the same as Example 1, except that: the perovskite film is prepared under an air humidity of 60%, and the p-type silicon substrate can be replaced by FTO conductive glass, n-type silicon, silicon dioxide, flexible substrate (such as PET or PEN material) or one of graphene as needed, and this replacement does not affect the final perovskite crystal formation. Fig. 9 Undoped MAPbI3 perovskite films deposited on different substrates.
[0062] Embodiment 4: The rest is the same as Embodiment 2, except that:
[0063] 0.1 mg of tetrabutylamine hexafluorophosphate and 50 μl of 2% PMMA chlorobenzene solution were added into 1 ml of toluene, and mixed evenly by magnetic stirring or ultrasound.
[0064] The methylamine halide raw material MABr is replaced by methylamine iodide MAI, and PbBr2 is replaced by a mixture of PbI2 and SnI2. The molar ratio of the mixture of PbI2 and SnI2 is 9:1. The obtained MAPb 0.9 Sn 0.1 The concentration of I3 in the perovskite precursor solution is 0.2 M.
[0065] The specific method of the two-step spin coating method is: dripping the perovskite precursor solution on the substrate, wherein the first step of spin coating takes 9 seconds and the spin coating speed is 1100 rpm, and the second step of spin coating takes 19 seconds and the spin coating speed is 5100 rpm. 9 seconds before the completion of the second step, the doped anti-solvent is dripped;
[0066] The annealing temperature is 95°C and the annealing time is 11 minutes. After completion, MAPb with good crystallization and long-term stable storage in air environment is obtained.0.9 Sn 0.1 I3 perovskite thin film. Fig.10 It is a perovskite film that is crystallized after doping. Fig.11 The comparison of photoluminescence intensity of perovskite film before and after doping. Fig.12 This is a comparison of the photoluminescence intensity of doped and undoped films after long-term exposure to air.
[0067] Embodiment 5: The rest is the same as Embodiment 2, except that:
[0068] 0.7 mg of tetrabutylamine hexafluorophosphate and 200 μl of 2% PMMA chlorobenzene solution were added into 1 ml of chlorobenzene, and mixed evenly by magnetic stirring or ultrasound.
[0069] The methylamine halide raw material MABr is doped with formamidine halide (CH(NH2)2I, FAI) and metal halide CsI, and PbBr2 is doped with PbI2. The molar ratios of PbI2 / PbBr2 and FAI / MABr are fixed at 0.95:0.05, the molar ratio of CsI / (FAI+MABr) is 0.05:0.95, and the molar ratio of (FAI+MABr+CsI) / (PbI2+PbBr2) is fixed at 1:1. 0.05 FA 0.9 MA 0.05 PbI 2.85 Br 0.15 The concentration in the perovskite precursor solution is 0.6 M.
[0070] The specific method of the two-step spin coating method is: dripping the perovskite precursor solution on the substrate, wherein the first step of spin coating lasts for 11 seconds and the spin coating speed is 950 rpm, and the second step of spin coating lasts for 21 seconds and the spin coating speed is 4900 rpm. 11 seconds before the completion of the second step, dripping the doped anti-solvent;
[0071] The annealing temperature is 105°C and the annealing time is 9 minutes. After completion, Cs with good crystallization and long-term stable storage in air environment is obtained. 0.05 FA 0.9 MA 0.05 PbI 2.85 Br 0.15 Perovskite thin films. Fig.13 It is a perovskite film that is crystallized after doping. Fig.14 The comparison of photoluminescence intensity of perovskite film before and after doping. Fig.15 This is a comparison of the photoluminescence intensity of doped and undoped films after long-term exposure to air.
[0072] Embodiment 6: The rest is the same as Embodiment 2, except that:
[0073] 0.4 mg of tetrabutylamine hexafluorophosphate and 150 μl of 2% PMMA chlorobenzene solution were added into 1 ml of ether, and mixed evenly by magnetic stirring or ultrasound.
[0074] The methylamine halide raw material MABr is replaced by a mixture of MAI and KCl, and PbBr2 is replaced by a mixture of PbCl2 and PbI2. 0.9 K 0.1 PbI 2.8 Cl 0.2 The concentration in the perovskite precursor solution is 0.5 M. The molar ratio of MAI to KCl is 9:1, the molar ratio of the mixture of PbI2 and PbCl2 is 1.9:0.1, and the molar ratio of (MAI+KCl) / (PbI2+SnI2) is kept fixed at 1:1.
[0075] The annealing temperature is 100°C and the annealing time is 9 minutes. After completion, a well-crystallized MA is obtained that can be stably stored in an air environment for a long time. 0.9 K 0.1 PbI 2.8 Cl 0.2 Perovskite thin films. Fig.16 It is a perovskite film that is crystallized after doping. Fig.17 The comparison of photoluminescence intensity of perovskite film before and after doping. Fig.18 This is a comparison of the photoluminescence intensity of doped and undoped films after long-term exposure to air.
[0076] The above embodiments are only for illustrating the technical idea of the present invention, and cannot be used to limit the protection scope of the present invention. Any changes made on the basis of the technical solution in accordance with the technical idea proposed by the present invention shall fall within the protection scope of the present invention; any technology not involved in the present invention can be realized by existing technologies.
Claims
1. A method for preparing a perovskite film in air, characterized in that: The method for preparing the perovskite film comprises four steps: (1) preparing a substrate and preparing a perovskite precursor solution; (2) doping and preparing an anti-solvent; (3) spin coating the perovskite on the substrate by a spin coating method; (4) annealing and crystallizing to form a perovskite film; the doping materials in the anti-solvent are tetrabutylammonium hexafluorophosphate and polymethyl methacrylate; In step (3), the spin coating of the perovskite precursor uses a two-step spin coating method, and the doped anti-solvent is added dropwise 9 to 11 seconds before the completion of the second step.
2. The method for preparing a perovskite film in air according to claim 1, characterized in that: The substrate is prepared specifically as follows: cutting the substrate into square substrates, cleaning the substrates using an RCA cleaning method, and then drying the substrates; The perovskite precursor solution is prepared by dissolving monovalent cation halide and lead halide and / or tin halide powders in a mixed solution of N,N-dimethylformamide and dimethyl sulfoxide, and rapidly dissolving them by magnetic stirring or ultrasound, wherein the concentration of monovalent cation lead halide and / or tin in the obtained perovskite precursor solution is 0.2-1M; The doping and preparation of the anti-solvent: tetrabutylamine hexafluorophosphate and 2% PMMA chlorobenzene solution are added to the anti-solvent, and mixed evenly by magnetic stirring or ultrasound, and the doping concentrations of the obtained solution are: 0.1-0.7 mg / ml tetrabutylamine hexafluorophosphate and 0.1%-0.4% PMMA; The annealing crystallization specifically includes: transferring the spin-coated substrate to a hot stage for annealing crystallization to form a perovskite film.
3. The method for preparing a perovskite film in air according to claim 2, characterized in that: The anti-solvent is one or more of toluene, chlorobenzene, dichloromethane, ethyl acetate or ether.
4. The method for preparing a perovskite film in air according to claim 2, characterized in that: The volume ratio of the N,N-dimethylformamide to dimethyl sulfoxide is 9:
1.
5. The method for preparing a perovskite film in air according to claim 2, characterized in that: The substrate is one of an ITO or FTO conductive glass substrate, p-type silicon, n-type silicon, silicon dioxide, a flexible substrate or graphene.
6. The method for preparing a perovskite film in air according to claim 2, characterized in that: The specific method of the two-step spin coating method is: dripping the perovskite precursor solution on the substrate, wherein the first step of spin coating takes 9 to 11 seconds and the spin coating speed is 950 to 1100 rpm, and the second step of spin coating takes 19 to 21 seconds and the spin coating speed is 4900 to 5100 rpm.
7. The method for preparing a perovskite film in air according to claim 2, characterized in that: The annealing crystallization temperature is 95-105° C., and the annealing time is 9-11 minutes. After completion, a well-crystallized perovskite film that can be stably stored for a long time in an air environment is obtained.
8. A perovskite crystalline material, characterized in that: The perovskite film is formed by annealing and crystallization by the method for preparing the perovskite film in the air as described in any one of claims 1 to 7, and the general formula of the perovskite crystalline material is ABX3, wherein A is a monovalent cation, B is a divalent metal cation, and X is a halogen anion.
9. A perovskite crystalline material according to claim 8, characterized in that: The monovalent cation is Rb + 、Na + , K + , Cs + 、(NH2)2CH + or CH3NH3 + One or more of; wherein the divalent metal cation is Pb 2+ and / or Sn 2+ ; The halogen anion is Cl - Br - and I - One or more of .
Citation Information
Patent Citations
Preparation method of red light two-dimensional perovskite film with high stability
CN109860428A
Perovskite solar cell with low trap state and preparation method thereof
CN113871536A
Cited By
Perovskite thin film constructed in situ based on thermal initiation fluorinated polymerization grid, and preparation method and application thereof
CN121127094A